Optimal Design of Ecological Landscape Spatial Structure Based on Edge Computing of Internet of Things. (7th March 2022) - An, Ru
Abstract : Ecological landscape space refers to a whole composed of many different ecosystems in a larger area. The spatial structure of the ecological landscape is the spatial arrangement and combination of the components and elements of the landscape. With the sustainable development of today's world, the procedure of urbanization is also accelerating. The urbanization procedure has significantly changed the types of urban landscapes and the spatial structure of urban landscapes, which will also produce corresponding ecological effects. No matter how good or bad the ecological effect is, it will have a certain impact on people's lives. Therefore, continuously promoting the majorization of the spatial structure of urban ecological landscape is a significant method to promise the healthy improvement of the city. This article is aimed at studying the optimal design of urban ecological landscape spatial structure based on edge computing of the Internet of Things. This paper uses city A as the experimental object to design a space structure majorization experiment of urban ecological landscape based on the edge computing of the Internet of Things, and the experiment draws a conclusion. The urban ecological landscape structure majorization plan based on the edge computing of the Internet of Things increases the biodiversity index of city A by 1.2, indicating that the method of optimizing the structure of the ecological landscape based on the edge computing of the Internet of Things has a better effect of optimizing the structure of the ecological landscape.